Bipolar radiofrequency ablation of refractory ventricular arrhythmias: results from a multicentre network - Futyma, Piotr; Sultan, Arian; Zarębski, Łukasz; Imnadze, Guram; Maslova, Vera; Bordignon, Stefano; Kousta, Maria; Knecht, Sven; Pavlović, Nikola; Peichl, Petr; Lian, Evgeny; Kueffer, Thomas; et al. (Europace, 2024)
AIMS: Advanced ablation strategies are needed to treat ventricular tachycardia (VT) and premature ventricular complexes (PVC) refractory to standard unipolar radiofrequency ablation (Uni-RFA). Bipolar radiofrequency catheter ablation (Bi-RFA) has emerged as a treatment option for refractory VT and PVC. Multicentre registry data on the use of Bi-RFA in the setting of refractory VT and PVC are lacking. The aim of this Bi-RFA registry is to determine its real-world safety, feasibility, and efficacy in patients with refractory VT/PVC. METHODS AND RESULTS: Consecutive patients undergoing Bi-RFA at 16 European centres for recurring VT/PVC after at least one standard Uni-RFA were included. Second ablation catheter was used instead of a dispersive patch and was positioned at the opposite site of the ablation target. Between March 2021 and August 2024, 91 patients underwent 94 Bi-RFA procedures (74 males, age 62 ± 13, and prior Uni-RFA range 1-8). Indications were recurrence of PVC (n = 56), VT (n = 20), electrical storm (n = 13), or PVC-triggered ventricular fibrillation (n = 2). Procedural time was 160 ± 73 min, Bi-RFA time 426 ± 286 s, and mean Uni-RFA time 819 ± 697 s. Elimination of clinical VT/PVC was achieved in 67 (74%) patients and suppression of VT/PVC in a further 10 (11%) patients. In the remaining 14 patients (15%), no effect on VT/PVC was observed. Three major complications occurred: coronary artery occlusion, atrioventricular block, and arteriovenous fistula. Follow-up lasted 7 ± 8 months. Nineteen patients (61%) remained VT free. ≥80% PVC burden reduction was achieved in 45 (78%). CONCLUSION: These real-world registry data indicate that Bi-RFA appears safe, is feasible, and is effective in the majority of patients with VT/PVC.
Keywords: recidiva; Registries; Humans; Premature ventricular complexes; lidé středního věku; registrace; studie proveditelnosti; Female; Aged; výsledek terapie; senioři; lidé; Europe; Advanced ablation strategies; katetrizační ablace; komorové extrasystoly; ženské pohlaví; Male; Ventricular Premature Complexes; Middle Aged; Treatment Outcome; Recurrence; komorová tachykardie; Feasibility Studies; Bipolar ablation; mužské pohlaví; Catheter Ablation; Ventricular tachycardia; Evropa; Tachycardia, Ventricular